3,4-Dihydroxyphenylacetate 2,3-dioxygenase from Pseudomonas aeruginosa: An Fe(II)-containing enzyme with fast turnover. - Soraya Pornsuwan; Somchart Maenpuen; Philaiwarong Kamutira; Pratchaya Watthaisong; Kittisak Thotsaporn; Chanakan Tongsook; Maneerat Juttulapa; Sarayut Nijvipakul; Pimchai Chaiyen (PLoS ONE)
3,4-dihydroxyphenylacetate (DHPA) dioxygenase (DHPAO) from Pseudomonas aeruginosa (PaDHPAO) was overexpressed in Escherichia coli and purified to homogeneity. As the enzyme lost activity over time, a protocol to reactivate and conserve PaDHPAO activity has been developed. Addition of Fe(II), DTT and ascorbic acid or ROS scavenging enzymes (catalase or superoxide dismutase) was required to preserve enzyme stability. Metal content and activity analyses indicated that PaDHPAO uses Fe(II) as a metal cofactor. NMR analysis of the reaction product indicated that PaDHPAO catalyzes the 2,3-extradiol ring-cleavage of DHPA to form 5-carboxymethyl-2-hydroxymuconate semialdehyde (CHMS) which has a molar absorptivity of 32.23 mM-1cm-1 at 380 nm and pH 7.5. Steady-state kinetics under air-saturated conditions at 25°C and pH 7.5 showed a Km for DHPA of 58 ± 8 μM and a kcat of 64 s-1, indicating that the turnover of PaDHPAO is relatively fast compared to other DHPAOs. The pH-rate profile of the PaDHPAO reaction shows a bell-shaped plot that exhibits a maximum activity at pH 7.5 with two pKa values of 6.5 ± 0.1 and 8.9 ± 0.1. Study of the effect of temperature on PaDHPAO activity indicated that the enzyme activity increases as temperature increases up to 55°C. The Arrhenius plot of ln(k'cat) versus the reciprocal of the absolute temperature shows two correlations with a transition temperature at 35°C. Two activation energy values (Ea) above and below the transition temperature were calculated as 42 and 14 kJ/mol, respectively. The data imply that the rate determining steps of the PaDHPAO reaction at temperatures above and below 35°C may be different. Sequence similarity network analysis indicated that PaDHPAO belongs to the enzyme clusters that are largely unexplored. As PaDHPAO has a high turnover number compared to most of the enzymes previously reported, understanding its biochemical and biophysical properties should be useful for future applications in biotechnology.